Structure and Dynamics of Alginate Gels Cross-Linked by Polyvalent Ions Probed via Solid State NMR Spectroscopy - Brus, Jiri; Urbanova, Martina; Czernek, Jiri; Pavelkova, Miroslava; Kubova, Katerina; Vyslouzil, Jakub; Abbrent, Sabina; Konefal, Rafal; Horský, Jiri; Vetchy, David; Vysloužil, Jan; Kulich, Pavel (Biomacromolecules, 2017)
Alginate gels are an outstanding biomaterial widely applicable in tissue engineering, medicine, and pharmacy for cell transplantation, wound healing and efficient bioactive agent delivery, respectively. This contribution provides new and comprehensive insight into the atomic-resolution structure and dynamics of polyvalent ion-cross-linked alginate gels in microbead formulations. By applying various advanced solid-state NMR (ssNMR) spectroscopy techniques, we verified the homogeneous distribution of the cross-linking ions in the alginate gels and the high degree of ion exchange. We also established that the two-component character of the alginate gels arises from the concentration fluctuations of residual water molecules that are preferentially localized along polymer chains containing abundant mannuronic acid (M) residues. These hydrated M-rich blocks tend to self-aggregate into subnanometer domains. The resulting coexistence of two types of alginate chains differing in segmental dynamics was revealed by 1H-13C dipolar profile analysis, which indicated that the average fluctuation angles of the stiff and mobile alginate segments were about 5-9° or 30°, respectively. Next, the 13C CP/MAS NMR spectra indicated that the alginate polymer microstructure was strongly dependent on the type of cross-linking ion. The polymer chain regularity was determined to systematically decrease as the cross-linking ion radius decreased. Consistent with the 1H-1H correlation spectra, regular structures were found for the gels cross-linked by relatively large alkaline earth cations (Ba2+, Sr2+, or Ca2+), whereas the alginate chains cross-linked by bivalent transition metal ions (Zn2+) and trivalent metal cations (Al3+) exhibited significant irregularities. Notably, however, the observed disordering of the alginate chains was exclusively attributed to the M residues, whereas the structurally well-defined gels all contained guluronic acid (G) residues. Therefore, a key role of the units in M-rich blocks as mediators promoting the self-assembly of alginate chains was experimentally confirmed. Finally, combining 2D 27Al 3Q/MAS NMR spectroscopy with density functional theory (DFT) calculations provided previously unreported insight into the structure of the Al3+ cross-linking centers. Notably, even with a low residual amount of water, these cross-linking units adopt exclusively 6-fold octahedral coordination and exhibit significant motion, which considerably reduces quadrupolar coupling constants. Thus, the experimental strategy presented in this study provides a new perspective on cross-linked alginate structure and dynamics for which high-quality diffraction data at the atomic resolution level are inherently unavailable.
Keywords: Glucuronic Acid; algináty; reagencia zkříženě vázaná; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Hydrogels; Cross-Linking Reagents; Alginates; kyselina glukuronová; kyseliny hexuronové; hydrogely; Hexuronic Acids